Ruthenium- and Rhodium-Catalyzed Ring-Opening Coupling Reactions of Cyclopropenones with Alkenes or Alkynes - Kondo, Teruyuki; Taniguchi, Ryosuke; Kimura, Yu (Synlett, 2018)
Ru3(CO)12-catalyzed divergent ring-opening coupling reactions of a cyclopropenone with methyl acrylate (an electron-deficient alkene) are developed. Under an argon atmosphere, a decarbonylative linear codimer is obtained, while cyclopentenones are obtained under carbon monoxide (20 atm) without decarbonylation. While ruthenium complexes show no catalytic activity for the ring-opening cocyclization of cyclopropenones with ethylene (20 atm) or bicyclo[2.2.1]hept-2-ene (2-norbornene), rhodium complexes, especially [RhCl(η4-1,5-cod)]2, show high catalytic activity for the desired cocyclization reactions to give the corresponding cyclopentenones in high yields and selectivities. In addition, [RhCl(η4-1,5-cod)]2 realizes the catalytic ring-opening cocyclization of cyclopropenones with internal alkynes to give the corresponding cyclopentadienones. In all these reactions, ruthena- or rhodacyclobutenones are considered to be key intermediates, generated by strain-driven oxidative addition of a cyclopropenone C–C bond to an active ruthenium or rhodium species.
Keywords: C–C bond cleavage; cyclopropenone; ruthenium; rhodium; cyclopentenone; cyclopentadienone; metallacyclic intermediate